Keterampilan Berpikir Kritis Siswa SMP dalam Menyelesaikan Masalah Kesebangunan Berdasarkan Kemampuan Matematika - Intan, Nuril; Ismail, Ismail; Susanah, Susanah (Universitas Negeri Surabaya, 2024)
The aim of this research is to describe junior high school students' critical thinking skills in solving congruence problems based on mathematical abilities. Critical thinking skills are a person's cognitive process in interpreting, analyzing, evaluating, inferring, explaining and self-regulating in the process of making reflective and focused judgments. This research is a qualitative descriptive study. The research took place at As - Syafiah Loceret Islamic Middle School, Nganjuk. Subjects were selected based on their level of mathematical ability, namely one student each with high, medium and low mathematical ability. Researchers act as the main instrument and data collector. Data collection techniques using mathematics ability tests, mathematics assignments, and semi-structured interviews. The research results showed that junior high school students in solving congruence problems demonstrated interpretation skills: categorization and decoding; analytical skills: examination of ideas, identification of arguments and analysis of arguments; evaluation skills : claim assessment and argument assessment; inference skills: questioning claims, alternative thinking and drawing conclusions, explanation skills: presentation of problems, justification of procedures and articulation of arguments, self-regulation skills: self-research. Students' critical thinking skills appear optimally in students with high mathematical abilities as evidenced by the emergence of all sub-indicators of critical thinking skills, less so in students with moderate mathematical abilities as evidenced by less than optimal identification of arguments for certain questions and the absence of alternative thinking for the mathematical tasks presented. Meanwhile, students with low mathematical abilities find it difficult so that their analysis, evaluation, inference, explanation and self-regulation skills are not perfect.